2020
DOI: 10.1016/j.isci.2020.101797
|View full text |Cite
|
Sign up to set email alerts
|

Human Dopaminergic Neurons Lacking PINK1 Exhibit Disrupted Dopamine Metabolism Related to Vitamin B6 Co-Factors

Abstract: Summary PINK1 loss-of-function mutations cause early onset Parkinson disease. PINK1-Parkin mediated mitophagy has been well studied, but the relevance of the endogenous process in the brain is debated. Here, the absence of PINK1 in human dopaminergic neurons inhibits ionophore-induced mitophagy and reduces mitochondrial membrane potential. Compensatory, mitochondrial renewal maintains mitochondrial morphology and protects the respiratory chain. This is paralleled by metabolic changes, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 92 publications
1
17
0
Order By: Relevance
“…This was independently confirmed in Parkin patient iPSC-derived dopamine neurons, with similar phenotypes observed in PINK1 patient neurons as well [ 43 ]. However, no altered mitochondrial morphology was observed in homozygous PINK1 knockout human dopaminergic neurons [ 99 ]. An increase in the numbers of elongated mitochondria in Parkin patient neurons was also reported by Bogetofte and colleagues [ 70 ].…”
Section: Discoveries Of Mitochondria-specific Phenotypes In Ipsc Models Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…This was independently confirmed in Parkin patient iPSC-derived dopamine neurons, with similar phenotypes observed in PINK1 patient neurons as well [ 43 ]. However, no altered mitochondrial morphology was observed in homozygous PINK1 knockout human dopaminergic neurons [ 99 ]. An increase in the numbers of elongated mitochondria in Parkin patient neurons was also reported by Bogetofte and colleagues [ 70 ].…”
Section: Discoveries Of Mitochondria-specific Phenotypes In Ipsc Models Of Pdmentioning
confidence: 99%
“…Similarly, stabilization of endogenous full-length PINK1 and increased ubiquitin phosphorylation was observed [ 149 , 151 ]. Finally, absence of PINK1 in human iPSC-derived dopaminergic neurons leads to inhibition of ionophore-induced mitophagy, providing further evidence for the role of PINK1 in this form of mitophagy [ 99 ].…”
Section: Discoveries Of Mitochondria-specific Phenotypes In Ipsc Models Of Pdmentioning
confidence: 99%
“…Research has shown that PINK1 deficiency impairs the differentiation of DA neurons from adult neural stem cells [34] and inhibits the mitophagy and MMP of DA neurons [35]. Knockout of PINK1 affects the neurotransmission of DA neurons and causes motor dysfunction in Drosophila [36].…”
Section: Discussionmentioning
confidence: 99%
“…B vitamins are directly involved in the proper functioning of the nervous system, including cognitive functions. Vitamin B6 (pyridoxine) affects the production of serotonin, dopamine, aminobutyric acid, increases the efficiency of thought processes, prevents apathy and insomnia [ 22 ]. Vitamin B12 (cobalamin) is involved in the formation of the myelin sheath [ 23 ].…”
Section: Natural Compoundsmentioning
confidence: 99%